2020
DOI: 10.1088/1361-6501/ab786b
|View full text |Cite
|
Sign up to set email alerts
|

Correction of spherical surface measurements by confocal microscopy

Abstract: Refractive microlenses are nowadays widely used in optical systems. Characterizing their surface is essential to ensure their quality and to optimize their fabrication process. This is realized by optical surface profilers thanks to their vertical resolution, short measurement time and areal information. However, when measuring non-flat surfaces, errors appear caused by aberrations of the microscope objective used in such systems, which significantly limit the achievable quality of the manufactured spherical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Confocal microscopy can also be used to improve and optimize the quality and the fabrication process of micro-lenses by correcting the errors from optical systems with a machine learning algorithm. In a study to correct the measurement error, an root mean square (RMS) wavefront error of λ/50 was successfully achieved for glass micro-lenses after applying the correction method [165].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Confocal microscopy can also be used to improve and optimize the quality and the fabrication process of micro-lenses by correcting the errors from optical systems with a machine learning algorithm. In a study to correct the measurement error, an root mean square (RMS) wavefront error of λ/50 was successfully achieved for glass micro-lenses after applying the correction method [165].…”
Section: Other Applicationsmentioning
confidence: 99%
“…However, this error can be corrected at a satisfactory level. 35,36 Consequently, the main drawback of these techniques is the limited capability to measure large and steep surfaces. This aspect is discussed in more detail in Sec.…”
Section: Surface Formmentioning
confidence: 99%
“…For the confocal measurement, it has been shown that this error can be corrected. 36 This comparison is summarized in Table 1. Information about measurement time is also included.…”
Section: Geometrical Limitationsmentioning
confidence: 99%
“…Mauch et al [ 13 ] explained in detail the signal formation process of the confocal system and proved that when the measured surface is curved, the defocusing wavefront may have a larger coincidence ratio than the focusing wavefront and the curvature of the measured surface, thus resulting in a large deviation in the axial position corresponding to the extreme value of the confocal signal strength. Beguelin et al [ 14 ] used machine-learning methods to compensate for errors caused by surface tilts in distance measurements and used imaging results to correct the measured data. Therefore, it is also important for the measurement of the spatial position to obtain the surface inclination while 3D spatial coordinates are concurrently obtained.…”
Section: Introductionmentioning
confidence: 99%